Efficient conversion of lignocellulosic biomass to levulinic acid using acidic ionic liquids - Khan, A.S. (Elsevier Ltd, 2018)
In the present research work, dicationic ionic liquids, containing 1,4-bis(3-methylimidazolium-1-yl) butane (C4(Mim)2) cation with counter anions (2HSO4)(H2SO4)0, (2HSO4)(H2SO4)2 and (2HSO4)(H2SO4)4 were synthesised. ILs structures were confirmed using 1H NMR spectroscopy. Thermal stability, Hammett acidity, density and viscosity of ILs were determined. Various types of lignocellulosic biomass such as rubber wood, palm oil frond, bamboo and rice husk were converted into levulinic acid (LA). Among the synthesized ionic liquids, C4(Mim)2(2HSO4)(H2SO4)4 showed higher % yield of LA up to 47.52 from bamboo biomass at 110 Â°C for 60 min, which is the better yield at low temperature and short time compared to previous reports. Surface morphology, surface functional groups and thermal stability of bamboo before and after conversion into LA were studied using SEM, FTIR and TGA analysis, respectively. This one-pot production of LA from agro-waste will open new opportunity for the conversion of sustainable biomass resources into valuable chemicals. Â© 2017